Does pre-emptive dexamethasone provide prophylaxis against sugammadex-induced bradycardia? A retrospective study - Jonathan S. Jahr; Pamela A. Chia; Tristan Grogan; Phiona Nansubuga; Julia Vogt; Victoria Klinewski; Thomas J. Ebert (PLoS ONE, 2025)
Sugammadex is a cyclodextrin used to reverse neuromuscular block with amino-steroid nondepolarizing muscle relaxants, rocuronium and vecuronium. Sugammadex-induced bradycardia was recently demonstrated in a single-blind, placebo-controlled study in patients receiving rocuronium for neuromuscular block. It has also been hypothesized that the bradycardia and rare instances of cardiac arrest occurring after the use of sugammadex may be due to a transient decrease in circulating corticosteroids, causing a temporary ‘mini Addisonian crisis.’ It was proposed that the administration of corticosteroids such as dexamethasone for post-operative nausea and vomiting (PONV) management might offer prophylaxis against these adverse occurrences. The study database was queried from a prospective study on sugammadex-related bradycardia, which was approved by the Human Studies Review Board and exempt from patient consent requirements. Patients were grouped into those that had or had not received dexamethasone as prophylaxis for PONV prior to the administration of sugammadex, and heart rate changes were evaluated 5 minutes after sugammadex administration. A total of 103 subjects were evaluated, of whom 38 received intravenous dexamethasone (either 4 mg, 8 mg, or 10 mg) during their anesthetic course and 65 patients had not received dexamethasone. The average heart rate (HR) slowing (3.2 bpm ± 3.9 in the control group, 3.7 bpm ± 3.8 in the dexamethasone group), and maximal HR slowing (5.0 bpm ± 3.9 in the control group, 5.0 bpm ± 3.8 in the dexamethasone group) over the five minutes following sugammadex administration were not significant between groups (average HR slowing p = 0.553, maximal HR slowing p = 0.988). These results potentially negate the proposed theory, or it may be that corticosteroids with more mineralocorticoid activity such as fludrocortisone or hydrocortisone are required to prevent this effect. Larger studies or prospective trials evaluating this effect with cortisol concentration measurement are needed to further evaluate the hypothesis.